X-ray photoelectron and infrared spectroscopies of quartz samples of contrasting toxicity - Richardson Neville V; Stephens W Edryd; Francis Stephen M (BMC, 2009)
Abstract An exploratory XPS and FTIR investigation of the surfaces of bulk quartz powders widely used in toxicological studies (DQ12 and Min-U-Sil 5) was carried with the aim of correlating surface features with toxicity as reflected by indicators of biological response. Some patches of amorphous silica were identified as well as varying amounts of calcium but none of these features correlated with biological response. No evidence of widely-quoted surface silanol (SiOH) structures was found in this investigation and the possibility that FTIR artefacts have been previously misidentified as silanol structures is discussed.